Computer-assisted Navigation in Bone Tumor Surgery: Seamless Workflow Model and Evolution of Technique - So, Timothy Y. C. (Springer-Verlag, 2010)
BACKGROUND: Computer-assisted navigation was recently introduced to aid the resection of musculoskeletal tumors. However, it has not always been possible to directly navigate the osteotomy with real-time manipulation of available surgical tools. Registration techniques vary, although most existing systems use some form of surface matching. QUESTIONS/PURPOSES: We developed and evaluated a workflow model of computer-assisted bone tumor surgery and evaluated (1) the applicability of currently available software to different bones; (2) the accuracy of the navigated excision; and (3) the accuracy of a new registration technique of fluoro-CT matching. METHODS: Our workflow involved detailed preoperative planning with CT-MRI image fusion, three-dimensional mapping of the tumor, and planning of the resection plane. Using the workflow model, we reviewed 15 navigation procedures in 12 patients, including four with joint-saving resections and three with custom implant reconstructions. Intraoperatively, registration was performed with either paired points and surface matching (Group 1, n = 10) or a new technique of fluoro-CT image matching (Group 2, n = 5). All osteotomies were performed under direct computer navigation. Postoperatively, each case was evaluated for histologic margin and gross measurement of the achieved surgical margin. RESULTS: The margins were free from tumor in all resected specimens. In the Group 1 procedures, the correlation between preoperative planned margins and actual achieved margins was 0.631, whereas in Group 2 procedures (fluoro-CT matching), the correlation was 0.985. CONCLUSIONS: Our findings suggest computer-assisted navigation is accurate and useful for bone tumor surgery. The new registration technique using fluoro-CT matching may allow more accurate resection of margins. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11999-010-1465-7) contains supplementary material, which is available to authorized users.